Propuesta de plan estratégico enfocado en la exportación de limón tahití, desde el municipio de Puerto Lopez - Meta hacia un mercado internacional europeo como opción de negocio (2024)
Colombia is a country that is identified and recognized for its agricultural production capacity, This being one of the main banana exporters worldwide, producing 3% of the world banana and occupying 9th place among exporters (Min agriculture, 2021). Without However, “Hass avocado, Tahiti lemon, gulupa, cape gooseberries and mangoes were the fruits with “higher sales abroad, between January and November 2023” (Forbes Colombia, February 1 2024, Colombian fresh fruit exports grew 5.1% in 2023). The Tahitian lemon has stood out in recent years as a highly requested fruit abroad, due to its different characteristics and uses such as gastronomic, cocktail, pharmaceutical and cosmetic. The Tahiti lemon is the third most exported agricultural product after bananas and hass avocado (Procolombia, 2022). According to agricultural change, the Tahiti lemon generated by 2022 US$76.6 million in exports, the main purchasing countries are the United States, Germany, Netherlands and Canada. By 2023, Tahiti lemon exports will close at US$96 million with an increase of 20% (ANALDEX,2023), which shows that it is a sector that has sustained its growth in the aforementioned periods. In Colombia, there is a climate and soil conditions suitable for cultivation and Tahiti lemon production, which makes it possible for Colombia to have more than 90,000 hectares planted with citrus fruits (DANE, 2021). In the goal, by 2021 it had an area planted with 5,584 hectares of citrus fruits and a production of 110,920 tons per year. In the Meta it occurs 6% of Tahiti export lemons (Procolombia, 2022), which due to its climate and soil make possible to meet the quality standards requested by foreign countries. Additionally, the export of agricultural products allows the department of meta diversify their sources of income, which are mainly oil exploitation and livestock (mayor of Villavicencio, 2018). Also, greater economic development of the agricultural sector is generated, thus contributing to the generation of employment in the villages and bringing new technologies to improve the processes that make possible the export of Tahiti lemon (Agro sap, 2023). On the other hand, the strengthening of the agricultural industry in the meta is significant potentiate the export of Tahiti lemon, since the operation transcends beyond cultivation and the exit of the merchandise, this points to the development of local agroindustrial capacities for processing and adding value to the product (Exposure, 2023). Furthermore, the adoption of cultivation and management techniques that minimize the environmental impact along with the adaptation of Quality certifications can contribute to more sustainable production (Minagro, 2022)